2020
DOI: 10.1149/1945-7111/ab8620
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Performance of Different Morphologies of LiNi0.8Mn0.1Co0.1O2 Using Isothermal Microcalorimetry, Ultra-High Precision Coulometry, and Long-Term Cycling

Abstract: Ni-rich positive electrode materials for Li-ion batteries have the dual benefit of achieving high energy density while reducing the amount of Co used in cells. However, limitations in cycle life are still an issue for the widespread adoption of these materials. The benefit of using single crystal materials has been demonstrated for LiNi0.5Mn0.3Co0.2O2 (NMC532), LiNi0.6Mn0.2Co0.2O2 (NMC622), and now LiNi0.8Mn0.1Co0.1O2 (NMC811). This work uses long-term cycling, ultra-high precision coulometry (UHPC), and isoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 43 publications
1
57
0
Order By: Relevance
“…3) and will undergo fewer electrolyte side reactions at the cathode. 4,16,27 Under these cycling conditions, the capacity fade occurs predominantly via lithium trapping in the SEI layer, as was found in other studies with these electrodes. 25 However, when the capacity fade based on the electrochemistry and cathode SoC measured using diffraction differ significantly, this indicates that the loss of lithium inventory (estimated based on x XRD ) cannot account for the capacity fade fully and there must be additional contributions.…”
Section: Discussionsupporting
confidence: 74%
“…3) and will undergo fewer electrolyte side reactions at the cathode. 4,16,27 Under these cycling conditions, the capacity fade occurs predominantly via lithium trapping in the SEI layer, as was found in other studies with these electrodes. 25 However, when the capacity fade based on the electrochemistry and cathode SoC measured using diffraction differ significantly, this indicates that the loss of lithium inventory (estimated based on x XRD ) cannot account for the capacity fade fully and there must be additional contributions.…”
Section: Discussionsupporting
confidence: 74%
“…[ 14 ] Furthermore, Dahn et al reported that a morphology consisting of the single particle cathode materials enhanced the thermal stability compared with that of polycrystalline cathode materials, which was attributed to the reduced surface area. [ 30 ] In terms of single‐crystalline NCM, the absence of an anisotropic volume change guarantees morphological integrity, preventing issues originating from intergranular crack generation.…”
Section: Figurementioning
confidence: 99%
“…In contrast, the polycrystal layered Ni‐rich cathode materials generally displayed the rapid capacity decay especially at high voltage and high temperature during long‐term cycling because of the serious crack generation triggered by the accumulation of heterogeneous stress. [ 8 ] Furthermore, the anode side also suffered from the transition metal (TM) reduction reaction on the surface, which can be attributed to the TM dissolution from polycrystal cathode side, further accelerating the cycling performance fade of pouch cells. [ 7a,8,9 ] Therefore, the design of single‐crystal morphology can be regarded as an effective strategy to improve the structural stability and electrochemical performances by means of unique features, including crack‐free, restrained side reactions, and limited gas generations, homogeneous internal stress, etc.…”
Section: Introductionmentioning
confidence: 99%